Trans-formation : FT* & MT*, 2010-2013 - Hélène Mourrier; Outrans (Glad!)
Sex change, i.e. reversing the established order of the feminine and the masculine, of genitals and genders, is not usually deemed a reasoned or sensible choice. FT * / MT *'s ambition is thus to give trans people an understanding of genital surgery, through an objective, moral-free standpoint. The role of this project is neither to encourage surgery nor to overlook trans claims, but to make visible what range of bodily transformations surgery currently allows. The construction and deconstruction of gender then exists through image itself; through this new activist representation our bodies are ours to manage.